Odpowiedzi

2009-12-01T17:03:15+01:00
Używaj entera

a) (x-2)²=x²
x²-4x+4=x²
x=1

b) (2x-2)²=4x(x-4)
4x²-8x+4=4x²-16x
8x=-4
x=-1/2
c) x(4x-3)=(2x-3)²
4x²-3x=4x²-12x+9
9x=9
x=1
d) x(0,04x-1,3)=(0,2x-1)²
0,04x²-1,3x=0,04x²-0,4x+1
-0,9x=1
x=-10/9
12 4 12
2009-12-01T17:12:03+01:00
A) (x-2)²=x²
x²-4x+4=x²
-4x=4/:(-4)
x=-1
b) (2x-2)²=4x(x-4)
4x²-8x+4=4x²-16x
-8x+16x=-4
8x=-4/:8
x=-0,5
c) x(4x-3)=(2x-3)²
4x²-3x=4x²-12x+9
-3x+12x=9
9x=9/:9
x=1
d) x(0,04x-1,3)=(0,2x-1)²
0,04x²-1,3x=0,04x²-0,4x+1
-1,3x+0,4x=1
-0,9x=1/:(-0,9)
x=-(1:0,9)
6 4 6
2009-12-01T17:23:48+01:00
A) (x-2)²=x²
x²-4x+4=x²
-4x+4=0
-4x=-4
x=1

(1-2)²=1²
1=1

b)(2x-2)²=4x(x-4)
4x²-8x+4=4x²-16x
-8x+4=-16x
-8x=4
x=-1/2

(-1-2)²=-2(-1/2-4)
9=9

c)x(4x-3)=(2x-3)²
4x²-3x=4x²-12x+9
-3x=-12x+9
9x=9
x=1

1(4-3)=(2-3)²
1=1

d)x(0,04x-1,3)=(0,2x-1)²
0,04x²-1,3x=0,04x²-0,4x+1
-1,3x=-0,4x+1
-0,9x=1 /:(-0,9)
x=-1/0,9
x=-10/9
x=-1¹/₉
5 4 5